Abstracts DEGRO 2018 Low-dose irradiation has an impact on bone metabolism as well as on local and systemic immune cell-mediated inflammation - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
Created from Fastlane, Scopus look-up

Abstracts DEGRO 2019 Niedrig dosierte Röntgenstrahlung beeinflusst die Makrophagenpolarisation im Zusammenspiel mit Synovialfibroblasten auf eine anti-entzündliche Art und Weise - Deloch, Lisa; Fuchs, Jana; Rückert, Michael; Frey, Benjamin; Gaipl, Udo (2019)
Created from Fastlane, Scopus look-up

Altered activation of the immune response causes radioresistance in HR-impaired breast cancer cells - Classen, S.; Rahlf, E.; Jungwirth, J.; Poole, L.; Gehre, S.; Rückert, Michael; Petersen, C.; Rothkamm, K.; Gaipl, Udo; Pospiech, H.; Borgmann, K. (RADIOTHERAPY AND ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Balancing barriers: Family, career, and gender equality in radiation oncology and radiation research—An interdisciplinary prospective survey among the young workforce - Trommer, Maike; Grohmann, Maximilian; Fabian, Alexander; Ehret, Felix; Hess, Julia; Rückert, Michael; Matschke, Johann; Stefanowicz, Sarah; Rühle, Alexander; Ferdinandus, Simone; Merten, Ricarda; Besserer, Angela; et al. (Strahlentherapie und Onkologie, 2025)
Purpose: There is an urgent need to recruit and retain young professionals in radiation oncology and radiation research as the healthcare system faces major challenges. Our study investigated the experiences and needs of young professionals in this field, focusing on the impact of unpaid care work and gender-related issues. Methods: A web-based survey was created and distributed over a six-week period, featuring one general questionnaire along with three occupation-specific versions tailored for physicians, biologists, and medical physicists involved in radiation oncology and research. Results: Most participants with care responsibilities have temporary contracts, especially female physicians and biologists, while female medical physicists are more likely to hold permanent positions. Research is often conducted outside regular hours, with limited cover arrangements and part-time options varying by field. Key career risks include economic pressure, work-life balance, and uncertain contracts, with employees with care duties feeling less supported overall. In addition, men seem to be more involved in care work and thus face unique challenges, such as insufficient career support and fears of poor future perspective. The study emphasizes the need for strategies to address relevant issues, such as flexible working arrangements, better mentoring support, and clear substitution policies that can ensure that young professionals can balance caring responsibilities with work and career demands. Conclusion: Addressing these challenges is critical for sustaining a diverse and qualified workforce in radiation oncology and radiation research, ensuring excellence in patient care and scientific progress.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Gender; Parity; Radiation oncology; Survey; Young workforce

Clonogenicity-based radioresistance determines the expression of immune suppressive immune checkpoint molecules after hypofractionated irradiation of MDA-MB-231 triple-negative breast cancer cells - Gehre, Simon; Meyer, Felix; Sengedorj, Azzaya; Grottker, Fridolin; Reichardt, Clara; Alomo, Jannik; Borgmann, Kerstin; Frey, Benjamin; Fietkau, Rainer; Rückert, Michael; Gaipl, Udo (Frontiers in Oncology, 2023)
Only a subset of patients with triple-negative breast cancer (TNBC) benefits from a combination of radio- (RT) and immunotherapy. Therefore, we aimed to examine the impact of radioresistance and brain metastasizing potential on the immunological phenotype of TNBC cells following hypofractionated RT by analyzing cell death, immune checkpoint molecule (ICM) expression and activation of human monocyte-derived dendritic cells (DCs). MDA-MB-231 triple-negative breast cancer tumor cells were used as model system. Apoptosis was the dominant cell death form of brain metastasizing tumor cells, while Hsp70 release was generally significantly increased following RT and went along with necrosis induction. The ICMs PD-L1, PD-L2, HVEM, ICOS-L, CD137-L and OX40-L were found on the tumor cell surfaces and were significantly upregulated by RT with 5 x 5.2 Gy. Strikingly, the expression of immune suppressive ICMs was significantly higher on radioresistant clones compared to their respective non-radioresistant ones. Although hypofractionated RT led to significant cell death induction and release of Hsp70 in all tumor cell lines, human monocyte-derived DCs were not activated after co-incubation with RT-treated tumor cells. We conclude that radioresistance is a potent driver of immune suppressive ICM expression on the surface of TNBC MDA-MB-231 cells. This mechanism is generally known to predominantly influence the effector phase, rather than the priming phase, of anti-tumor immune responses.
CRIS-Team Scopus Importer:2023-05-19
Keywords: breast cancer; dendritic cells; immune checkpoint molecules; radioresistance; radiotherapy; tumor cell death

Combinations of radiotherapy with vaccination and immune checkpoint inhibition differently affect primary and abscopal tumor growth and the tumor microenvironment - Rückert, Michael; Deloch, Lisa; Frey, Benjamin; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo (Cancers, 2021)
Radiotherapy (RT) is known to have immune‐modulatory properties. We hypothesized that RT and inactivated whole tumor cell vaccines generated with high hydrostatic pressure (HHP) synergize to retard the tumor growth which can be additionally improved with anti‐PD‐1 treatment. In abscopal tumor models, we injected mice with B16‐F10 melanoma or TS/A mammary tumors. To evaluate the efficiency of RT in combination with HHP vaccines, we locally irradiated only one tumor with 2 × 8 Gy or 3 × 8 Gy. HHP vaccines further retarded the growth of locally irradiated (2 × 8 Gy) tumors. However, HHP vaccination combined with RT failed to induce abscopal anti‐tumor immune responses, namely those to non‐irradiated tumors, and even partly abrogated those which were induced with RT plus anti‐PD‐1. In the latter group, the abscopal effects were accompanied by an elevated infiltration of CD8+ T cells, monocytes/macrophages, and dendritic cells. 3 × 8 Gy failed to induce abscopal effects in association with increased expression of immunosuppressive checkpoint molecules compared to 2 × 8 Gy. We conclude that HHP vaccines induce anti‐tumor effects, but only if the tumor microenvironment was previously modulated by hypofractionated RT with not too many fractions, but failed to improve RT plus anti‐PD‐induced abscopal responses that are characterized by distinct immune alterations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Abscopal effect; High hydrostatic pressure; Immune checkpoint inhibition; Radiotherapy; Tumor microenvironment; Tumor‐infiltrating immune cells; Vaccination

Creation of an Electro-magnetic Heat Simulation for Planning Hyperthermia Treatments for Mice - Kahlert, B.; Bert, Christoph; Rückert, Michael; Hensel, Bernhard; Root, Konstantin; Vossiek, Martin; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Detailed in vitro analyses of the impact of multimodal cancer therapy with hyperthermia and radiotherapy on the immune phenotype of human glioblastoma cells - Stoll, Eileen; Hader, Michael; Rückert, Michael; Weissmann, Thomas; Lettmaier, Sebastian; Putz, Florian; Hecht, Markus; Fietkau, Rainer; Rosin, Andreas; Frey, Benjamin; Gaipl, Udo (International Journal of Hyperthermia, 2022)
Purpose Improvements of heat-delivery systems have led to hyperthermia (HT) being increasingly recognized as an adjunct treatment modality also for brain tumors. But how HT affects the immune phenotype of glioblastoma cells is only scarcely known. Materials and Methods We therefore investigated the effect of in vitro HT, radiotherapy (RT), and the combination of both (RHT) on cell death modalities, immune checkpoint molecule (ICM) expression and release of the danger signal HSP70 of two human glioblastoma cell lines (U87 and U251) by using multicolor flow cytometry and ELISA. Hyperthermia was performed once or twice for 60-minute sessions reaching temperatures of 39 degrees C, 41 degrees C, and 44 degrees C, respectively. RT was administered with 5 x 2 Gy. Results A hyperthermia chamber for cell culture t-flasks regulating the temperature via a contact sensor was developed. While the glioblastoma cells were rather radioresistant, particularly in U251 cells, the combination of RT with HT significantly increased the percentage of apoptotic and necrotic cells for all temperatures examined and for both, single and double HT application. In line with that, an increased release of HSP 70 was seen only in U251 cells, mainly following treatment with HT at temperatures of 44 degrees C alone or in combination with RT. In contrast, immune suppressive (PD-L1, PD-L2, HVEM) and immune stimulatory (ICOS-L, CD137-L and Ox40-L) ICMs were significantly increased mostly on U87 cells, and particularly after RHT with 41 degrees C. Conclusions Individual assessment of the glioblastoma immune cell phenotype with regard to the planned treatment is mandatory to optimize multimodal radio-immunotherapy protocols including HT.
CRIS-Team WoS Importer:2022-06-24
Keywords: Hyperthermia; radiotherapy; immune checkpoint molecules; danger signals; glioblastoma; multimodal cancer therapy

Effect of hyperthermia and radiation therapy sequence on cell death and the immune phenotype of breast cancer cells - Sengedorj, Azzaya; Hader, Michael; Rückert, Michael; Frey, Benjamin; Fietkau, Rainer; Ott, Oliver; Scheidegger, S.; Barba, S. M.; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effect of micro- and nanoplastic particles on human macrophages - Adler, Maike-Yvonne; Issoual, Insaf; Rückert, Michael; Deloch, Lisa; Meier, Carola; Tschernig, Thomas; Alexiou, Christoph; Pfister, Felix; Ramsperger, Anja FRM; Laforsch, Christian; Gaipl, Udo; Jüngert, Katharina; et al. (Journal of Hazardous Materials, 2024)
Micro- and nanoplastics (MNPs) are ubiquitous in the environment, resulting in the uptake of MNPs by a variety of organisms, including humans, leading to particle-cell interaction. Human macrophages derived from THP-1 cell lines take up Polystyrene (PS), a widespread plastic. The question therefore arises whether primary human macrophages also take up PS micro- and nanobeads (MNBs) and how they react to this stimulation. Major aim of this study is to visualize this uptake and to validate the isolation of macrophages from peripheral blood mononuclear cells (PBMCs) to assess the impact of MNPs on human macrophages. Uptake of macrophages from THP-1 cell lines and PBMCs was examined by transmission electron microscopy (TEM), scanning electron microscopy and live cell imaging. In addition, the reaction of the macrophages was analyzed in terms of metabolic activity, cytotoxicity, production of reactive oxygen species (ROS) and macrophage polarization. This study is the first to visualize PS MNBs in primary human cells using TEM and live cell imaging. Metabolic activity was size- and concentration-dependent, necrosis and ROS were increased. The methods demonstrated in this study outline an approach to assess the influence of MNP exposure on human macrophages and help investigating the consequences of worldwide plastic pollution.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Live cell imaging; Macrophages; MNPs; Polystyrene beads; Transmission electron microscopy

Effect of Radiotherapy and Chemotherapy on the Immunophenotype of Head and Neck Cancer Cells and the consecutive Activation of dendritic Cells - Grottker, F.; Frey, Benjamin; Gehre, S.; Reichardt, Clara; Sengedorj, Azzaya; Hecht, Markus; Fietkau, Rainer; Rieckmann, T.; Gostian, Antoniu-Oreste; Gaipl, Udo; Rückert, Michael (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effects of BRCA1 Mutations on Radiation Resistance and Immunophenotype in Breast Cancer Cells - Classen, S.; Rahlf, E.; Jungwirth, J.; Gehre, S.; Rückert, Michael; Rothkamm, K.; Petersen, C.; Gaipl, Udo; Pospiech, H.; Borgmann, K. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effects of Radiotherapy on the Kinetics of Immune Checkpoint Molecule Expression in Tumor Cells and their radioresistant Clones - Siegert, Juliane; Rückert, Michael; Meyer, F.; Borgmann, K.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Head and neck tumor cells treated with hypofractionated irradiation die via apoptosis and are better taken up by M1-like macrophages - Wedekind, Hanna; Walz, Kristina; Buchbender, Mayte; Rieckmann, Thorsten; Strasser, Erwin; Grottker, Fridolin; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Rückert, Michael (Strahlentherapie und Onkologie, 2021)
Purpose: The incidence of head and neck squamous cell carcinomas (HNSCC) is increasing worldwide, especially when triggered by the human papilloma virus (HPV). Radiotherapy has immune-modulatory properties, but the role of macrophages present in HNSCC and having contact with irradiated tumor cells remains unclear. The influence of irradiated (2 × 5Gy) HNSCC cells on the (re-)polarization and phagocytosis of human macrophages, either non-polarized or with a more M1 or M2 phenotype, was therefore investigated. Methods: Human monocytes were differentiated with the hematopoietic growth factors M‑CSF (m) or GM-CSF (g) and additionally pre-polarized with either interleukin (IL)-4 and IL-10 or interferon (IFN)-γ and lipopolysaccharides (LPS), respectively. Subsequently, they were added to previously irradiated (2 × 5Gy) and mock-treated HPV-positive (UD-SCC-2) and HPV-negative (Cal33) HNSCC cells including their supernatants. Results: The HNSCC cells treated with hypofractionated irradiation died via apoptosis and were strongly phagocytosed by M0m and M2 macrophages. M0g and M1 macrophages phagocytosed the tumor cells to a lesser extent. Irradiated HNSCC cells were better phagocytosed by M1 macrophages compared to mock-treated controls. The polarization status of the macrophages was not significantly changed, except for the expression of CD206 on M2 macrophages, which was reduced after phagocytosis of irradiated HPV-negative cells. Further, a significant increase in the uptake of irradiated HPV-positive cells by M0g macrophages when compared to HPV-negative cells was observed. Conclusion: HNSCC cells treated with hypofractionated irradiation foster phagocytosis by anti-tumorigenic M1 macrophages. The data provide the first evidence on the impact of the HPV status of HNSCC cells on the modulation of the macrophage response to irradiated tumor cells.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Head and neck cancer; Human papilloma virus; Macrophage polarization; Phagocytosis; Radiotherapy

Hypofractionated Irradiation increases the Expression of the Immune Checkpoint Molecule HVEM on TS/A, 4T1-luc and E0771 Breast Carcinoma Cells - Flohr, Ann-Sophie; Fietkau, Rainer; Rückert, Michael; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Hypofractionated Radiation increases the Expression of the Immune Checkpoint-Molecule HVEM on TS/A Breast Cancer- and B16 Melanoma Cells - Flohr, Ann-Sophie; Grün, A; Fietkau, Rainer; Rückert, Michael; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Immune modulation during anti-cancer radio(immuno)therapy - Irianto, Teresa Tamara; Gaipl, Udo; Rückert, Michael (International Review of Cell and Molecular Biology, 2023)
Cancer can affect all human organs and tissues and ranks as a prominent cause of death as well as an obstruction to increasing life expectancy. A notable breakthrough in oncology has been the inclusion of the immune system in fighting cancer, potentially prolonging life and providing long-term benefits. The concept of “immunotherapy” has been discussed from the 19th and early 20th centuries by Wilhelm Busch, William B. Coley and Paul Ehrlich. This involves distinct approaches, including vaccines, non-specific cytokines and adoptive cell therapies. However, despite the advances made in recent years, questions on how to select the best therapeutic options or how to select the best combinations to improve clinical outcomes are still relevant for scientists and clinicians. More than half of cancer patients receive radiotherapy (RT) as part of their treatment. With the advances in RT and immunotherapy approaches, it is reasonable to consider how to enhance immunotherapy with radiation and vice versa, and to investigate whether combinations of these therapies would be beneficial. In this chapter, we will discuss how the immune system responds to cancer cells and different cancer therapies with a focus on combination of RT and immunotherapy (radioimmunotherapy, RIT).
CRIS-Team Scopus Importer:2023-08-11
Keywords: Immune checkpoint molecules; Immune editing; Immunogenic cell death; Radioimmunotherapies; Radiotherapy

Impact of radio(chemo)therapy on expression of immune checkpoint ligands PD-L1 and PD-L2 on murine and human melanoma cells - Riegel, Dania; Bäumler, Monika; Spiljar, Martina; Rückert, Michael; Frey, Benjamin; Fietkau, Rainer; Derer, Anja; Gaipl, Udo (DEGRO - Deutsche Gesellschaft für Radioonkologie e.V., 2017)
EVALuna2:32890

Interaction of Radiotherapy and Hyperthermia with the Immune System: a Brief Current Overview - Sengedorj, Azzaya; Hader, Michael; Frey, Benjamin; Fietkau, Rainer; Ott, Oliver; Gaipl, Udo; Rückert, Michael (Current Stem Cell Reports, 2022)
Purpose of Review This review focuses on the opposing effects on the immune system of radiotherapy (RT) and the consequences for combined cancer treatment strategies of RT with immunotherapies, including hyperthermia (HT). How RT and HT might affect cancer stem cell populations is also briefly outlined in this context.
CRIS-Team WoS Importer:2022-07-29

LOCAL LOW DOSE RADIATION INDUCES SYSTEMIC IMMUNE ALTERATIONS IN TWO EXPERIMENTAL MODELS OF INFLAMMATORY ARTHRITIS - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Low-dose irradiation has an impact on bone metabolism as well as on local and systemic immune cell-mediated inflammation - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36495

LOW DOSE RADIATION ALTERS THE INFLAMMATORY PHENOTYPE OF FIBROBLAST-LIKE SYNOVIOCYTES AND MACROPHAGES AND STIMULATES OSTEOBLASTS - Deloch, Lisa; Liberg, Jana; Rückert, Michael; Hueber, Axel; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2017)
EVALuna2:32907

LOW DOSE RADIATION HAS A POSITIVE IMPACT ON BONE METABOLISM IN AN EXPERIMENTAL MODEL OF INFLAMMATORY ARTHRITIS - Deloch, Lisa; Rückert, Michael; Hueber, Axel; Herrmann, Martin; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36516

Low-Dose Radiotherapy Has No Harmful Effects on Key Cells of Healthy Non-Inflamed Joints - Deloch, Lisa; Rückert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Molecular Sciences, 2018)
Low-dose radiotherapy (LD-RT) for benign inflammatory and/or bone destructive diseases has been used long. Therefore, mechanistic investigations on cells being present in joints are mostly made in an inflammatory setting. This raises the question whether similar effects of LD-RT are also seen in healthy tissue and thus might cause possible harmful effects. We performed examinations on the functionality and phenotype of key cells within the joint, namely on fibroblast-like synoviocytes (FLS), osteoclasts and osteoblasts, as well as on immune cells. Low doses of ionizing radiation showed only a minor impact on cytokine release by healthy FLS as well as on molecules involved in cartilage and bone destruction and had no significant impact on cell death and migration properties. The bone resorbing abilities of healthy osteoclasts was slightly reduced following LD-RT and a positive impact on bone formation of healthy osteoblasts was observed after in particular exposure to 0.5 Gray (Gy). Cell death rates of bone-marrow cells were only marginally increased and immune cell composition of the bone marrow showed a slight shift from CD8⁺ to CD4⁺ T cell subsets. Taken together, our results indicate that LD-RT with particularly a single dose of 0.5 Gy has no harmful effects on cells of healthy joints.
EVALuna2:36453

Low-Dose Radiotherapy Leads to a Systemic Anti-Inflammatory Shift in the Pre-Clinical K/BxN Serum Transfer Model and Reduces Osteoarthritic Pain in Patients - Weissmann, Thomas; Rückert, Michael; Zhou, Jianguo; Seeling, Michaela; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Nimmerjahn, Falk; Ott, Oliver; Hecht, Markus; Putz, Florian; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2022)
Osteoarthritis (OA) is the leading degenerative joint disease in the western world and leads, if left untreated, to a progressive deterioration of joint functionality, ultimately reducing quality of life. Recent data has shown, that especially OA of the ankle and foot are among the most frequently affected regions. Current research in OA points towards a complex involvement of various cell and tissue types, often accompanied by inflammation. Low-dose radiotherapy (LDRT) is widely used for the treatment of degenerative and inflammatory diseases. While the reported analgesic effects are well known, the underlying molecular mechanisms are only poorly understood. We therefore correlated a clinical approach, looking at pain reduction in 196 patients treated with LDRT with a pre-clinical approach, utilizing the K/BxN serum transfer mouse model using flow cytometry and multiplex ELISA for analysis. While an improvement of symptoms in the majority of patients was found, patients suffering from symptoms within the tarsi transversa show a significantly lower level of improvement. Further, a significant impact of therapy success was detected depending on whether only one or both feet were affected. Further, patients of younger age showed a significantly better outcome than older ones while needing fewer treatment series. When looking on a cellular level within the mouse model, a systemic alteration of immune cells namely a shift from CD8+ to CD4+ T cells and reduced numbers of DCs was observed. A general reduction of inflammatory cytokines was detected, with significant alterations in IL-4 and IL-17 levels, all of which could potentially be responsible for the highly effective clinical improvement in patients. Taken together our data indicate that LDRT can be regarded as a highly effective treatment option for patients suffering from OA of the foot and ankle, in terms of analgesic effects, especially in younger patients. Furthermore, the observed effects are mediated by an interplay of cellular and soluble immune factors, as observed in the K/BxN serum transfer model. With this interdisciplinary approach we aim to encourage the usage of LDRT as an additive treatment strategy not only as a last resort, but also earlier in the course of disease.
CRIS-Team Scopus Importer:2022-01-28
Keywords: foot; K/BxN serum transfer; low-dose radiotherapy; mouse model; osteoarthritis; pain; rheumatoid arthritis; X-rays

Low-dose radiotherapy of osteoarthritis: from biological findings to clinical effects-challenges for future studies - Weissmann, Thomas; Rückert, Michael; Putz, Florian; Donaubauer, Anna-Jasmina; Hecht, Markus; Schnellhardt, Sören; Schubert, Philipp; Roesch, Johannes; Höfler, Daniel; Ott, Oliver; Haderlein, Marlen; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2023)

Low-dose Radiotherapy with X-rays and Radon leads to different immunological Changes in a Mouse Model for Rheumatoid Arthritis - Deloch, Lisa; Rückert, Michael; Maier, A.; Hinrichs, A.; Weissmann, T.; Seeling, Michaela; Nimmerjahn, Falk; Flohr, A. -S.; Eckert, D.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Mucosal tumor vaccination delivering endogenous tumor antigens protects against pulmonary breast cancer metastases - Oltmanns, Friederike; Vieira Antao, Ana Isabel; Irrgang, Pascal; Viherlehto, Vera; Jörg, Leticia; Schmidt, Anna; Wagner, Jannik; Rückert, Michael; Flohr, Ann-Sophie; Geppert, Carol-Immanuel; Frey, Benjamin; Bayer, Wibke; et al. (Journal for ImmunoTherapy of Cancer, 2024)
Background Generally, early-stage breast cancer has a good prognosis. However, if it spreads systemically, especially with pulmonary involvement, prospects worsen dramatically. Importantly, tumor-infiltrating T cells contribute to tumor control, particularly intratumoral T cells with a tissue-resident memory phenotype are associated with an improved clinical outcome. Methods Here, we use an adenoviral vector vaccine encoding endogenous tumor-associated antigens adjuvanted with interleukin-1β to induce tumor-specific tissue-resident memory T cells (TRM) in the lung for the prevention and treatment of pulmonary metastases in the murine 4T1 breast cancer model. Results The mucosal delivery of the vaccine was highly efficient in establishing tumor-specific TRM in the lung. Concomitantly, a single mucosal vaccination reduced the growth of pulmonary metastases and improved the survival in a prophylactic treatment. Vaccine-induced TRM contributed to these protective effects. In a therapeutic setting, the vaccination induced a pronounced T cell infiltration into metastases but resulted in only a minor restriction of the disease progression. However, in combination with stereotactic radiotherapy, the vaccine increased the survival time and rate of tumor-bearing mice. Conclusion In summary, our study demonstrates that mucosal vaccination is a promising strategy to harness the power of antitumor TRM and its potential combination with state-of-the-art treatments.
CRIS-Team Scopus Importer:2024-03-22

Neutrophils seeking new neighbors: radiotherapy affects the cellular framework and the spatial organization in a murine breast cancer model - Reichardt, Clara; Munoz Becerra, Marco; Rius Rigau, Aleix Rius; Rückert, Michael; Fietkau, Rainer; Schett, Georg; Gaipl, Udo; Frey, Benjamin; Munoz Becerra, Luis (Cancer Immunology, Immunotherapy, 2024)
Neutrophils are known to contribute in many aspects of tumor progression and metastasis. The presence of neutrophils or neutrophil-derived mediators in the tumor microenvironment has been associated with poor prognosis in several types of solid tumors. However, the effects of classical cancer treatments such as radiation therapy on neutrophils are poorly understood. Furthermore, the cellular composition and distribution of immune cells in the tumor is of increasing interest in cancer research and new imaging technologies allow to perform more complex spatial analyses within tumor tissues. Therefore, we aim to offer novel insight into intra-tumoral formation of cellular neighborhoods and communities in murine breast cancer. To address this question, we performed image mass cytometry on tumors of the TS/A breast cancer tumor model, performed spatial neighborhood analyses of the tumor microenvironment and quantified neutrophil-extracellular trap degradation products in serum of the mice. We show that irradiation with 2 × 8 Gy significantly alters the cellular composition and spatial organization in the tumor, especially regarding neutrophils and other cells of the myeloid lineage. Locally applied radiotherapy further affects neutrophils in a systemic manner by decreasing the serum neutrophil extracellular trap concentrations which correlates positively with survival. In addition, the intercellular cohesion is maintained due to radiotherapy as shown by E-Cadherin expression. Radiotherapy, therefore, might affect the epithelial–mesenchymal plasticity in tumors and thus prevent metastasis. Our findings underscore the growing importance of the spatial organization of the tumor microenvironment, particularly with respect to radiotherapy, and provide insight into potential mechanisms by which radiotherapy affects epithelial–mesenchymal plasticity and tumor metastasis.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Cancer; Cellular neighborhood; Image mass cytometry; Neutrophil; Radiotherapy

P22-2-jD Mit hydrostatischem Hochdruck generierte Ganzzell- Tumorvakzine erzeugen in Kombination mit Strahlentherapie ein immunogenes Tumor-Mikromilieu - Rückert, Michael; Seitz, Christoph; Deloch, Lisa; Weiss, Eva-Maria; Utz, S; Izydor, Marika; Ebel, Nina; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2019)

Radioresistance shapes the immunogenic Properties of Triple-negative Breast Cancer Cells - Gehre, S.; Rückert, Michael; Sengedorj, Azzaya; Grottker, F.; Reichardt, Clara; Meyer, F.; Borgmann, K.; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Radiotherapy and the immune system: More than just immune suppression - Rückert, Michael; Flohr, Ann-Sophie; Hecht, Markus; Gaipl, Udo (Stem Cells, 2021)
Radiotherapy (RT) is still one of the standard cancer therapies with up to two third of all cancer patients with solid tumors being irradiated in the course of their disease. The aim of using ionizing radiation in fractionated treatment schedules was always to achieve local tumor control by inducing DNA damage which can be repaired by surrounding normal tissue but leads to cell death in tumor cells. Meanwhile, it is known that RT also has immunological effects reshaping the tumor microenvironment. Nevertheless, RT alone often fails to elicit potent antitumor immune responses as these effects can be immunostimulatory as well as immunosuppressive. Here, we discuss how immunotherapies can be exploited in combined therapies to boost RT-induced antitumor immune responses or to counteract preexisting and RT-mediated immunosuppression to improve local and systemic tumor control. Furthermore, we highlight some parameters of radioimmunotherapies (RITs) which are under investigation for potential optimizations and how RIT approaches are tested in first phases II and III trials. Finally, we discuss how RT might affect normal and cancer stem cells.
CRIS-Team WoS Importer:2021-05-28

Radiotherapy combined with docetaxel alters the immune phenotype of HNSCC cells and results in increased surface expression of CD137 and release of HMGB1 of specifically HPV-positive tumor cells - Grottker, Fridolin; Gehre, Simon; Reichardt, Clara; Sengedorj, Azzaya; Jost, Tina; Rieckmann, Thorsten; Hecht, Markus; Gostian, Antoniu-Oreste; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Rückert, Michael (Neoplasia, 2023)
Purpose: Human papilloma virus (HPV) positive head and neck squamous cell carcinoma (HNSCC) tumors respond significantly better to anticancer treatments. It is assumed to be due to a better response to radiotherapy (RT), and presumably to an increased immunogenicity. However, little is known how the immune phenotype of HNSCC tumor cells is modulated by standard treatment, namely by radiochemotherapy (RCT). Methods: Therefore, we aimed to examine the impact of the HPV status on the immune phenotype of HNSCC cell lines following RCT with 5 × 3Gy or 1 × 19.3Gy and/or docetaxel, by analyzing cell death, release of damage-associated molecular patterns (DAMPs), surface expression of immune checkpoint molecules (ICMs) and the impact on activation of human monocyte-derived dendritic cells (hmDCs). Results: Cell death induction and Hsp70 release following RCT was independent of the HPV status, and RCT significantly increased the expression of the immune suppressive ICMs PD-L1, PD-L2 and HVEM. An immune stimulatory ICM, CD137, was significantly increased following RCT only on HPV-positive cell lines, as well as the release of HMGB1. Although the treatment increased cell death and modulated ICM expression in HNSCC, the hmDCs were not activated after co-incubation with treated tumor cells. Conclusion: Our data with the HPV-dependent release of HMGB1 and increased expression of CD137 following RCT provide a hint for increased immunogenicity underlining the better prognosis for HPV positive tumors following RCT.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Anti-tumor immunity; Dendritic cells; Docetaxel; Head and neck squamous cell carcinoma; HMGB1; HPV status; Immune checkpoint molecules; Radiotherapy

Radon affects Immune Cells ex vivo as well as in vivo in an Animal Model of experimental Arthritis - Deloch, Lisa; Rückert, Michael; Maier, A.; Hinrichs, A.; Flohr, Ann-Sophie; Eckert, D.; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Fournier, C.; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Radon Improves Clinical Response in an Animal Model of Rheumatoid Arthritis Accompanied by Increased Numbers of Peripheral Blood B Cells and Interleukin-5 Concentration - Deloch, Lisa; Hehlgans, Stephanie; Rückert, Michael; Maier, Andreas; Hinrichs, Annika; Flohr, Ann-Sophie; Eckert, Denise; Weissmann, Thomas; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Rödel, Franz; et al. (Cells, 2022)
Radon treatment is used as an established therapy option in chronic painful inflammatory diseases. While analgesic effects are well described, little is known about the underlying molecular effects. Among the suspected mechanisms are modulations of the anti-oxidative and the immune system. Therefore, we aimed for the first time to examine the beneficial effects of radon exposure on clinical outcome as well as the underlying mechanisms by utilizing a holistic approach in a controlled environment of a radon chamber with an animal model: K/BxN serum-induced arthritic mice as well as isolated cells were exposed to sham or radon irradiation. The effects on the anti-oxidative and the immune system were analyzed by flow-cytometry, qPCR or ELISA. We found a significantly improved clinical disease progression score in the mice, alongside significant increase of peripheral blood B cells and IL-5. No significant alterations were visible in the anti-oxidative system or regarding cell death. We conclude that neither cell death nor anti-oxidative systems are responsible for the beneficial effects of radon exposure in our preclinical model. Rather, radon slightly affects the immune system. However, more research is still needed in order to fully understand radon-mediated effects and to carry out reasonable risk-benefit considerations.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Anti-oxidative system; B cells; Immune system; Inflammation; Macrophages; Monocytes; Radon therapy; Rheumatoid arthritis; Serum transfer arthritis; T cells

The Effect of Hyperthermia and Radiotherapy Sequence on Cancer Cell Death and the Immune Phenotype of Breast Cancer Cells - Sengedorj, Azzaya; Hader, Michael; Heger, Lukas; Frey, Benjamin; Dudziak, Diana; Fietkau, Rainer; Ott, Oliver; Scheidegger, Stephan; Barba, Sergio Mingo; Gaipl, Udo; Rückert, Michael (Cancers, 2022)
Hyperthermia (HT) is an accepted treatment for recurrent breast cancer which locally heats the tumor to 39–44◦C, and it is a very potent sensitizer for radiotherapy (RT) and chemotherapy. However, currently little is known about how HT with a distinct temperature, and particularly, how the sequence of HT and RT changes the immune phenotype of breast cancer cells. Therefore, human MDA-MB-231 and MCF-7 breast cancer cells were treated with HT of different temperatures (39, 41 and 44◦C), alone and in combination with RT (2 × 5 Gy) in different sequences, with either RT or HT first, followed by the other. Tumor cell death forms and the expression of immune checkpoint molecules (ICMs) were analyzed by multicolor flow cytometry. Human monocyte-derived dendritic cells (moDCs) were differentiated and co-cultured with the treated cancer cells. In both cell lines, RT was the main stressor for cell death induction, with apoptosis being the prominent cell death form in MCF-7 cells and both apoptosis and necrosis in MDA-MB-231 cells. Here, the sequence of the combined treatments, either RT or HT, did not have a significant impact on the final outcome. The expression of all of the three examined immune suppressive ICMs, namely PD-L1, PD-L2 and HVEM, was significantly increased on MCF-7 cells 120 h after the treatment of RT with HT of any temperature. Of special interest for MDA-MB-231 cells is that only combinations of RT with HT of both 41 and 44◦C induced a significantly increased expression of PD-L2 at all examined time points (24, 48, 72, and 120 h). Generally, high dynamics of ICM expression can be observed after combined RT and HT treatments. There was no significant difference between the different sequences of treatments (either HT + RT or RT + HT) in case of the upregulation of ICMs. Furthermore, the co-culture of moDCs with tumor cells of any treatment had no impact on the expression of activation markers. We conclude that the sequence of HT and RT does not strongly affect the immune phenotype of breast cancer cells. However, when HT is combined with RT, it results in an increased expression of distinct immune suppressive ICMs that should be considered by including immune checkpoint inhibitors in multimodal tumor treatments with RT and HT. Further, combined RT and HT affects the immune system in the effector phase rather than in the priming phase.
CRIS-Team Scopus Importer:2022-04-29
Keywords: breast cancer; dendritic cell activation; hyperthermia; hyperthermia treatment sequence; immune checkpoint molecules; immune phenotype; radiotherapy

The Growth of primary and abscopal Tumors as well as their immunological Microenvironment are differently influenced by different Combinations of Radiation and Immunotherapies - Rückert, Michael; Deloch, Lisa; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The various functions and phenotypes of macrophages are also reflected in their responses to irradiation: A current overview - Deloch, Lisa; Rückert, Michael; Weissmann, Thomas; Lettmaier, Sebastian; Titova, Eva; Wolff, Teresa; Weinrich, Felix; Fietkau, Rainer; Gaipl, Udo (International Review of Cell and Molecular Biology, 2023)
Macrophages are a vital part of the innate immune system that are involved in healthy biological processes but also in disease modulation and response to therapy. Ionizing radiation is commonly used in the treatment of cancer and, in a lower dose range, as additive therapy for inflammatory diseases. In general, lower doses of ionizing radiation are known to induce rather anti-inflammatory responses, while higher doses are utilized in cancer treatment where they result, next to tumor control, in rather inflammatory responses. Most experiments that have been carried out in ex vivo on macrophages find this to be true, however in vivo, tumor-associated macrophages, for example, show a contradictory response to the respective dose-range. While some knowledge in radiation-induced modulations of macrophages has been collected, many of the underlying mechanisms remain unclear. Due to their pivotal role in the human body, however, they are a great target in therapy and could potentially aid in better treatment outcome. We therefore summarized the current knowledge of macrophage mediated radiation responses.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Immune cells; Immunology; Low-dose radiotherapy; Macrophage polarization; Macrophages; Radiotherapy; Rheumatoid arthritis; Tumor associated macrophages